Palladium-Catalyzed Unimolecular Fragment Coupling of N-Allylamides Bearing a Tethered Nucleophile with the Translocation of an Amide Group - Shimazumi, Ryoma; Kodama, Takuya; Tobisu, Mamoru (Synthesis, 2023)
The palladium-catalyzed reaction of N-allylamides bearing a tethered nucleophile results in the extrusion of an amide moiety in the form of an isocyanate, with its subsequent capture by the pendant nucleophile. This reaction involves the net catalytic transposition of an amide group.
Keywords: palladium catalyst; C–N bond activation; amides; isocyanates; elimination; rearrangement